Langues, plurilinguismes, publics enseignés : quelles conceptions pour quels (dé)cloisonnements des usages didactiques dans un paysage mondialisé ? - Maxime Alais; Léa Courtaud; Joanna Lorilleux; François Girardeau (Recherches en didactique des langues et des cultures)
Based on research carried out in a variety of contexts (UPE2A / DASPA; European / bi-national sections / CLIL; AEFE network; internationalized universities), this article looks at how conceptions of the public and of languages feed into the ways of thinking about these institutional arrangements, and into the practices and representations of teachers and learners. More concretely, it examines the ways in which linguistic and cultural plurality is recognized, notably through the teaching content used, and the attention paid (or not paid) to linguistic repertoires and epistemic, scholastic and educational traditions. From a cross-cutting and historical perspective, the aim is to find keys to understanding the constitution of the various networks involved (DASPA-UPE2A, bilingual sections, AEFE, internationalized universities) and the socio-political issues at stake against a backdrop of globalization. The article takes a fresh look at the usual conceptions that assign students to distinct roles according to the underlying representations of the plurilingualism.